Management of information through an interactive voice response system the prospect of religious domain - Embong, Abdullah; Jamaludin, Zulikha (2004)
This paper explores the potential of using an interactive voice response system to maange information in institutions of religious domain. We first explain the terminologies involved such as an interactive voice response system, computer telephony integration, information management, and religious domain. Then we look at how information is managed through an interactive voice response system. IVR application supports two kinds of communications, i.e. real time communication and message type communication. Users could make either a real time communication or a message type communication as needed. Real time communication includes accessing databases in order to get instant and updated information within the real time during the call is made through the system. Message type communication includes voice mail application using telephone recording. The suitability of using interactive voice response for institution of religious domain is studied, and we also describe a few options for the implementation of the system.